Ternary precursor and preparation method thereof, positive electrode material
By designing the structure of a multi-layer connection layer in the ternary precursor positive electrode material, the structural problems caused by volume changes during the charging and discharging process are solved, the compressive resistance and lithium ion conduction ability are improved, the battery life is extended and the performance is improved.
Patent Information
- Application Number
- CN202310018392.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-06
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-01-06
AI Technical Summary
The existing ternary precursor positive electrode material particles have inconsistent volume changes during charging and discharging, resulting in structural cracks and reducing battery service life, cycle performance and safety performance.
A ternary precursor material is designed, which includes a core layer, a shell layer and a multi-layer connecting layer between the core layer and the shell layer. The core layer and the shell layer are dense structures and the connecting layer are loose structures. By adjusting the porosity and thickness of the connecting layer, the compressive resistance and lithium ion conduction ability of the material are improved.
It improves the compressive resistance and structural stability of the ternary precursor material particles, enhances the lithium ion conduction ability, extends the battery life, and improves the circulation and safety performance.
Smart Images

Figure CN116119735B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a ternary precursor and a preparation method thereof, and a positive electrode material. Background Art
[0002] With the rapid development of the world's automobile industry, green new energy vehicles have gradually become the future development direction of the industry. New energy vehicles use lithium batteries as their core power. How to improve the endurance and energy storage capacity of lithium batteries, the energy density per unit volume of lithium battery materials, battery safety performance, and service life has become a trend and a technological trend. As an important component of lithium batteries, ternary precursor positive electrode materials have always been the core of technology. Since core-shell materials have excellent characteristics of high capacity, good cycle and rate, most of the current ternary precursor materials are core-shell structures.
[0003] At present, the core-shell structured ternary precursor material particles generally have a porous gap ring layer between the core layer and the shell layer, so that the inside of the particle is in full contact with the electrolyte, which is conducive to the conduction of lithium ions, thereby improving the material cycle performance, reducing the battery resistance, and increasing the battery capacity and service life. However, during use, with long-term repeated charging and discharging, the volume changes of the core and shell materials of different components and different ingredients of the ternary precursor material particles during the charging and discharging process are inconsistent. The stress generated by the irreversible change of volume will cause cracks in the particle structure, resulting in a shortened battery life, poor cycle performance and poor safety performance. In particular, when a porous gap ring layer is set between the core layer and the shell layer, on the one hand, the thickness of the single layer ring layer cannot be set too large to avoid the continuous wide porous gap structure between the core layer and the shell layer, resulting in insufficient compressive resistance; on the other hand, if there is no ring layer, although the particle structure strength is higher, the contact area between the particle and the electrolyte is reduced, which will affect the lithium ion conduction ability and reduce the battery performance.
[0004] Therefore, it is particularly important to set a connecting layer between the core layer and the shell layer that has both excellent compressive resistance and lithium ion conductivity. Summary of the invention
[0005] In response to at least some of the problems of traditional ternary precursor positive electrode material particles, such as weak structural compressive resistance, insufficient contact between the particles and the electrolyte, and poor material cycle performance, the present invention provides a ternary precursor and its preparation method, and a positive electrode material, which can improve the compressive resistance and structural stability of the ternary precursor material particles, while ensuring that the material has better lithium ion conductivity.
[0006] According to one aspect of the present invention, a ternary precursor is provided, the chemical formula of the ternary precursor is Ni x Co y Mn z Ma (OH)2, wherein 0.75≤x<1.0, 0≤y<0.18, 0≤z<0.20, 0≤a<0.1, x+y+z+a=1; M is at least one of Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr.
[0007] The ternary precursor includes a core layer, a shell layer and multiple connecting layers between the core layer and the shell layer. The core layer and the shell layer are dense structures, and all the connecting layers are loose structures.
[0008] In the above technical scheme of the present invention, the dense core layer and the dense shell layer have fewer pores, lower porosity, and higher relative density, while the loose connection layer has a porous fluffy structure, higher porosity, and lower relative density. The use of a multi-layer loose porous structure connection layer can make the interior of the particle fully contact with the electrolyte, increase the lithium ion conduction speed, thereby reducing resistance, improving rate performance and cycle stability. At the same time, the multi-layer loose connection layer can buffer and accommodate the stress caused by the volume change of the particles during charging and discharging, and the dense and compact core layer and the dense shell layer structure can withstand the stress generated by the cyclic charge and discharge, improve the material's compressive resistance and structural stability, thereby improving the life and safety performance of the battery. In addition, the ternary precursor provided by this scheme is a high-nickel product, which has the advantages of good cycle performance, high energy density, stability and good safety performance.
[0009] In a further preferred embodiment, the ternary precursor includes a core layer, a first connecting layer, an intermediate layer, a second connecting layer and a shell layer from the inside to the outside, and the first connecting layer, the intermediate layer and the second connecting layer are all loose structures.
[0010] In the above technical scheme of the present invention, the ternary precursor is a core-shell structure, which specifically includes a core layer, a first connecting layer, an intermediate layer, a second connecting layer and a shell layer from the inside to the outside. The first connecting layer, the intermediate layer and the second connecting layer between the core layer and the shell layer are designed to be a porous loose structure, which is beneficial to increase the reaction area between the ternary precursor material and the electrolyte, so that the lithium ion conduction between the core layer and the shell layer is smoother, thereby reducing resistance, improving rate performance and cycle stability, and the first connecting layer, the intermediate layer and the second connecting layer are designed to be a porous loose structure, which is beneficial to reduce or alleviate the stress caused by the volume change of the material during the charge and discharge process. Combined with the core layer with a dense structure of the outer layer and the shell layer with a dense structure, the compressive strength and structural stability of the particles can be improved, thereby improving the life of the battery.
[0011] In a further preferred embodiment, the porosity of the intermediate layer is less than the porosity of the first connecting layer, and the porosity of the first connecting layer is less than or equal to the porosity of the second connecting layer.
[0012] Since the first connecting layer is arranged outside the core layer and inside the middle layer, by controlling the porosity of the first connecting layer to be greater than the porosity of the middle layer, that is, the first connecting layer is a loose porous structure with more pores, the first connecting layer can provide a lithium ion conduction channel for the core layer and the middle layer, which is beneficial to the conduction of lithium ions; since the second connecting layer is arranged outside the middle layer and inside the shell layer, by controlling the porosity of the second connecting layer to be greater than the porosity of the middle layer, that is, the second connecting layer is a loose porous structure with more pores, the second connecting layer can provide a lithium ion conduction channel for the middle layer and the shell layer, which is beneficial to the conduction of lithium ions; since the first connecting layer is located closer to the central core layer of the particle, and the second connecting layer is located away from the central core layer of the particle, by controlling the porosity of the first connecting layer to be less than the second connecting layer, it is more beneficial to the stability of the overall structure of the particle.
[0013] Moreover, since the structure of the intermediate layer is denser than that of the first connecting layer and the second connecting layer, the intermediate layer can reinforce the first connecting layer and the second connecting layer, thereby improving the strength of the particle structure; at the same time, the first connecting layer and the second connecting layer can effectively reduce and alleviate the stress caused by the internal volume change of the particles during charging and discharging, thereby avoiding particle damage and cracking that affects the battery cycle performance and service life.
[0014] In a further preferred embodiment, the porosity of the first connecting layer is 6.84%-24.85%, the porosity of the second connecting layer is 7.02%-27.33%, and the porosity of the intermediate layer is 2.27%-10.89%;
[0015] In this solution, by limiting the porosity of the first connecting layer, the middle layer and the second connecting layer, it can ensure that the first connecting layer, the middle layer and the second connecting layer have good lithium ion conductivity, and at the same time it is beneficial to improve the compression resistance and structural stability of the particles and increase the life of the battery.
[0016] In a further preferred embodiment, the porosity of the first connecting layer is 9.20%-20.07%, the porosity of the second connecting layer is 9.99%-21.78%, and the porosity of the middle layer is 3.41%-8.44%, which is beneficial to further improve the lithium ion conduction capacity and connection strength of the first connecting layer, the middle layer and the second connecting layer.
[0017] In a further preferred embodiment, the average radius of the core layer is 0.90-2.90 μm; the average thickness of the first connecting layer is 0.69-0.92 μm; the average thickness of the intermediate layer is 1.38-1.85 μm; the average thickness of the second connecting layer is 1.03-1.39 μm; and the average thickness of the shell layer is 2.75-3.69 μm.
[0018] The thickness of the core layer, the first connecting layer, the middle layer, the second connecting layer and the shell layer is determined according to the particle size of the particle growth cycle. The core layer and the shell layer within the above thickness range can greatly improve the strength and compressive resistance of the particle structure. Moreover, by controlling the appropriate thickness of the first connecting layer, the middle layer and the second connecting layer of the loose structure, the lithium ion conduction and stress relief functions of the first connecting layer, the middle layer and the second connecting layer will not be affected, and the problem of collapse of the particle structure caused by excessive thickness can be avoided.
[0019] In a further preferred embodiment, the primary particles constituting the core layer, the first connecting layer, the intermediate layer and the second connecting layer are all in the shape of needle strips, and the primary particles constituting the shell layer are in the shape of needle strips or strips;
[0020] The primary particles constituting the intermediate layer and the shell layer grow radially.
[0021] The intermediate layer and shell layer of the present scheme grow radially along the radial direction of the core layer, and cooperate with the first connecting layer and the second connecting layer to make the lithium ion conduction in the inner and outer layers of the particles smoother. In addition, the primary particles constituting the core layer, the first connecting layer, the intermediate layer, the second connecting layer and the shell layer are all needle-shaped, which is further beneficial to increase the lithium ion conduction speed, reduce the positive electrode resistance, and improve the rate performance and cycle stability.
[0022] In a further preferred embodiment, the particle size D50 of the ternary precursor is 13.5-21.5 μm, and (D90-D10) / D50 is 0.2-0.4;
[0023] Preferably, the particle size D50 of the ternary precursor is 15.5-19.5 μm, and (D90-D10) / D50 is 0.25-0.35.
[0024] The particle size range of this solution is extremely narrow and the particles are more crystalline, which can ensure that the core-shell structure of the ternary precursor is as strong as possible, which is beneficial to the stability of the structural strength. At the same time, it does not affect the lithium ion conduction ability and electrical conductivity of the ternary precursor after it is made into a ternary positive electrode material.
[0025] In a further preferred embodiment, the specific surface area of the ternary precursor is 12-20 m 2 / g; within the specific surface area range of this scheme, it is possible to avoid excessive contact between the ternary precursor material particles and the electrolyte to produce side reactions, thereby preventing the side reactions from damaging the structure of the ternary precursor material without affecting the lithium ion conduction capability.
[0026] Preferably, the specific surface area of the ternary precursor is 13-19 m 2 / g, at this time, the problem of side reactions between the ternary precursor material particles and the electrolyte causing damage to the structure of the ternary precursor material can be further avoided.
[0027] In a further preferred embodiment, the tap density of the ternary precursor is 1.73-2.13 g / cm 3 ; Within the tap density range of this scheme, it can withstand the stress generated by the particles during the charging and discharging process, improve the compressive resistance of the particles, and enhance the structural stability.
[0028] Preferably, the tap density of the ternary precursor is 1.83-2.03 g / cm 3 At this time, the stress generated by the particles during the charging and discharging process can be further improved, the particles' ability to withstand pressure can be improved, and the structural stability can be enhanced.
[0029] According to another aspect of the present invention, a method for preparing a ternary precursor is provided, comprising the following steps: adding a ternary mixed solution containing nickel, cobalt and manganese into a reaction kettle, adding a pH regulator and a complexing agent to adjust the reaction solution to a first pH value and a first ammonia concentration, and introducing a protective gas to perform a first reaction to prepare a seed crystal;
[0030] After the first reaction is completed, the feed flow rate of the ternary mixed solution is changed, and the reaction solution is adjusted to a second pH value and a second ammonia concentration to perform a second reaction until a ternary precursor is obtained.
[0031] In the above technical scheme of the present invention, a first reaction is carried out under certain reaction conditions, and after the first reaction, a core layer with a loose center and a dense outer layer is formed, so that the core layer has a certain compressive resistance, and then the reaction conditions are changed to carry out a second reaction. During the second reaction, a loose first connecting layer, an intermediate layer, a second connecting layer and a dense shell layer are formed in stages outside the core layer, thereby obtaining a ternary precursor material with multiple layers of loose porous connecting layers and a dense outer shell structure. This method can form connecting layers with different pores outside the core layer by adjusting the feed flow rate of the ternary mixed solution, and by adjusting the reaction stirring intensity, pH and ammonia concentration, the supersaturation of the reaction solution can be reduced, which is conducive to the growth of crystals on the interface, thereby forming a dense structure, enhancing the material's compressive resistance, and improving the structural stability of the ternary precursor material.
[0032] In a further preferred embodiment, the feed rate of the first reaction is 3.0-6.0% / h; the feed rate of the second reaction is 1.0-8.5% / h; wherein, the feed rate of 3.0-6.0% / h means that the feed rate of the ternary mixed solution is 3.0-6.0% / h of the effective volume of the reactor, that is, the volume of the ternary mixed solution added per hour accounts for 3.0-6.0% of the effective volume of the reactor. The second reaction includes a first stage, a second stage, a third stage and a fourth stage. During the reaction process of the first stage, the second stage, the third stage and the fourth stage, the feed rate of the ternary mixed solution in each stage increases stepwise on the basis of the feed rate of the previous stage, and the stepwise increase ratio is 2%-100%. Preferably, the stepwise increase ratio is 5%-100%.
[0033] In this scheme, the reaction rates of the first reaction and the second reaction can be increased by regulating the feed flow rate of the ternary mixed solution of the first reaction and the second reaction. In addition, by adjusting the feed flow rate, pH and other reaction conditions of the ternary mixed solution at different stages during the second reaction, a first connecting layer, an intermediate layer, a second connecting layer and a shell layer with different porosities can be formed. Thus, the first connecting layer, the intermediate layer, the second connecting layer and the dense shell layer with loose structures can be used to improve the compressive strength and structural stability of the prepared ternary precursor material particles, while ensuring that the material has better lithium ion conductivity.
[0034] In a further preferred embodiment, the molar ratio of nickel, cobalt and manganese in the ternary mixed solution is x:y:z, wherein 0.75≤x<1.0, 0≤y<0.18, 0≤z<0.20, x+y+z=1;
[0035] Preferably, the total concentration of nickel, cobalt and manganese metal ions in the ternary mixed solution is 90-130 g / L.
[0036] More preferably, it can be doped, and the doping element M is at least one of Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr. The doping element can be in the form of sulfate or chloride.
[0037] The high-nickel ternary precursor material prepared by this scheme has the advantages of low cost, good cycle performance, high energy density, good stability and safety performance.
[0038] In a further preferred embodiment, the first pH value is adjusted to gradually decrease during the first reaction, and the second pH value is adjusted to gradually increase during the first stage, second stage, third stage and fourth stage of the second reaction. Specifically, the pH value of the first stage remains unchanged and is less than the pH value of the second stage; the pH value of the second stage is increased and remains unchanged and is less than the pH value of the third stage; the pH value of the third stage is increased and remains unchanged and is less than the pH value of the fourth stage, and the pH of the fourth stage is kept unchanged. This is conducive to the growth of crystals on the interface, thereby quickly forming a first connecting layer, an intermediate layer, a second connecting layer and a dense shell layer of a loose structure.
[0039] Preferably, the first pH value and the second pH value are both 10.0-12.0, which is conducive to the rapid growth of the core layer, the first connecting layer, the intermediate layer, the second connecting layer and the shell layer particles, thereby obtaining a ternary precursor material with a multi-layer porous connecting layer and a dense shell structure.
[0040] Preferably, the endpoint pH value of the first pH value is 0.1-0.3 lower than the initial pH value of the first pH value, that is, the initial pH of the first reaction is 0.1-0.3 lower than the endpoint pH of the first reaction. By controlling the degree of pH reduction, it is beneficial to quickly form a core layer with a loose center and a dense outer layer.
[0041] Preferably, the endpoint pH value of the second pH value is 0.1-0.4 higher than the initial pH value of the second pH value, that is, the pH value of the fourth stage is 0.1-0.4 higher than the pH value of the first stage. By controlling the degree of pH increase, the particles can grow uniformly and the consistency and connection strength of the particles can be improved.
[0042] Preferably, the pH regulator includes one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate, and soda ash; using these alkaline substances as pH regulators can effectively adjust the pH, and the raw materials are widely available and the materials are simple and easy to obtain.
[0043] Preferably, the pH regulator is a sodium hydroxide aqueous solution with a mass fraction of 25%-60%. The sodium hydroxide aqueous solution in the concentration range of this solution can effectively regulate the pH of the reaction solution to facilitate the rapid growth of particles.
[0044] In a further preferred embodiment, the first ammonia concentration and the second ammonia concentration are 2.0-7.5 g / L; by controlling the ammonia concentration, it is beneficial to the rapid growth of the core layer, the first connecting layer, the middle layer, the second connecting layer and the shell layer particles, thereby obtaining a ternary precursor material with a multi-layer porous connecting layer and a dense shell structure.
[0045] Preferably, the second ammonia concentration is 1.0-3.0 g / L higher than the first ammonia concentration. By controlling the degree of increase in ammonia concentration, the particles can grow uniformly, and the consistency and connection strength of the particles can be improved.
[0046] Preferably, the complexing agent includes one or more of ammonia water, EDTA, ethylenediamine, sodium citrate, and urea. These complexing agents can be used to effectively control the ammonia concentration of the reaction solution, so as to accelerate the growth rate of the particles. In addition, the raw materials of the complexing agent are widely available and the materials are simple and easy to obtain.
[0047] Preferably, the complexing agent is ammonia water with a mass fraction of 15%-45%, which can further accelerate the growth rate of the particles.
[0048] In a further preferred embodiment, the reaction temperature during the first reaction and the second reaction is the same;
[0049] Preferably, the reaction temperature during the first reaction and the second reaction is 45-70°C.
[0050] By controlling the reaction temperatures of the first reaction and the second reaction to be appropriate and to remain constant, it is beneficial for the various layers of the ternary precursor to grow evenly and ensure stable particle strength.
[0051] In a further preferred embodiment, the first reaction and the second reaction are carried out while stirring, and the stirring speed in the first reaction remains unchanged, while the stirring speed in the second reaction gradually decreases as the reaction proceeds;
[0052] Preferably, the stirring speed of the first reaction is 200-240 r / min, the stirring speed of the second reaction is 30-200 r / min, and the stirring speed at the end of the second reaction is reduced to 30-100 r / min.
[0053] During the second reaction, the stirring speed is gradually reduced to reduce the supersaturation of the reaction solution, which is beneficial to the growth of crystals on the interface, thereby quickly forming the first connecting layer, the middle layer, the second connecting layer and the shell layer.
[0054] In a further preferred embodiment, the seed particle size D50 after the first reaction is completed is 1.8-5.8 μm;
[0055] Preferably, the seed crystal particle size D50 after the first reaction is completed is 2.8-4.8 μm.
[0056] Within the particle size range of this scheme, a core layer with a loose center and a dense outer layer can be formed after the first reaction is completed. The formed core layer can effectively buffer the volume strain of the inner and outer layers during the cyclic charge and discharge process, while ensuring the structural strength and compressive resistance of the ternary precursor particles.
[0057] In a further preferred embodiment, the particle size D50 of the ternary precursor after the second reaction is completed is 13.5-21.5 μm;
[0058] Preferably, the particle size D50 of the ternary precursor after the second reaction is completed is 15.5-19.5 μm.
[0059] Within the particle size range of this scheme, after the second reaction is completed, a loose first connecting layer, an intermediate layer, a second connecting layer and a dense shell layer can be formed in sequence outside the core layer. The formed first connecting layer, intermediate layer, second connecting layer and shell layer can improve the lithium ion conductivity inside the particles, while improving the compression resistance and structural stability of the particles, thereby improving the battery life, rate performance and cycle stability.
[0060] According to another aspect of the present invention, a battery positive electrode material is provided, which is prepared by mixing and sintering any of the above-mentioned ternary precursors with a lithium salt. The prepared battery positive electrode material can improve the lithium ion conduction efficiency when used in a battery, thereby improving the material cycle performance, reducing the battery resistance, and improving the battery capacity, service life, cycle performance and safety performance.
[0061] According to another aspect of the present invention, a battery positive electrode is provided, comprising the above-mentioned battery positive electrode material. The battery positive electrode prepared by the above-mentioned battery positive electrode material is beneficial to improving the use effect of the battery.
[0062] According to another aspect of the present invention, a lithium ion battery is provided, comprising the above-mentioned battery positive electrode. The lithium ion battery assembled by the above-mentioned battery positive electrode has the advantages of low resistance, large capacity, long service life, high cycle performance and safety performance.
[0063] According to another aspect of the present invention, there is provided an electrical equipment, comprising the above-mentioned lithium-ion battery, by which the above-mentioned lithium-ion battery can be used to stably supply power to the corresponding electrical equipment, thereby ensuring continuous and stable operation of the equipment.
[0064] In summary, the ternary precursor and preparation method thereof, and the positive electrode material provided by the present invention have at least the following characteristics:
[0065] Beneficial effects:
[0066] The ternary precursor material with a multi-layer porous connecting layer and dense shell structure provided by the present invention has a core layer and a shell layer, and there are two connecting layers with different porosities and an intermediate layer with a certain porosity between the core layer and the shell layer, the surface layer of the core layer is a dense structure and the shell layer is a dense structure; the porosity of the intermediate layer is less than the porosity of the first connecting layer, the porosity of the first connecting layer is less than or equal to the porosity of the second connecting layer, the particles of the intermediate layer grow radially and are connected to the core layer via the first connecting layer, and are connected to the shell layer via the second connecting layer, and the structures of each layer cooperate with each other, so that the lithium ion conduction inside the particles of the ternary precursor material is smoother, and the first connecting layer and the second connecting layer with two different porosities are conducive to increasing the reaction area with the electrolyte and improving the lithium ion conduction speed, thereby significantly reducing the positive electrode resistance and improving the rate performance and cycle stability. At the same time, the two porous connecting layers can buffer and accommodate the stress caused by the volume change during charging and discharging, and the dense core layer and the dense radial structure shell of the material can withstand the stress generated by cyclic charging and discharging, improve the compressive resistance and structural stability, thereby increasing the life of the battery and improving the initial charging and discharging efficiency and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0068] Figure 1 is a schematic structural diagram of a ternary precursor provided by an embodiment of the present invention;
[0069] Figure 2 is a cross-sectional view of the ternary precursor provided in Example 1;
[0070] Figure 3 is a cross-sectional view of the ternary precursor provided in Example 2;
[0071] Figure 4 is a cross-sectional view of the ternary precursor provided in Example 3;
[0072] Figure 5 is a cross-sectional view of the ternary precursor provided in Example 4;
[0073] Figure 6 is a cross-sectional view of the ternary precursor provided in Comparative Example 1;
[0074] Figure 7 is a cross-sectional view of the ternary precursor provided in Comparative Example 2;
[0075] Figure 8This is a cross-sectional view of the ternary precursor provided in Example 3.
[0076] Figure 1 In the figure, there is a core layer 100, a first connection layer 200, an intermediate layer 300, a second connection layer 400, and a shell layer 500. DETAILED DESCRIPTION
[0077] It should be understood that the specific embodiments given herein are for the purpose of explaining to those skilled in the art and are merely illustrative rather than restrictive.
[0078] In the following description, many specific details are set forth to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that specific details need not be adopted to practice the present invention. In other cases, well-known steps or operations are not described in detail to avoid obscuring the present invention.
[0079] Reference Figure 1 As shown, the ternary precursor provided by the embodiment of the present invention includes a core layer 100, a first connecting layer 200, an intermediate layer 300, a second connecting layer 400 and a shell layer 500 from the inside to the outside. The core layer 100 is a loose structure in the center and a dense structure in the outer layer. The first connecting layer 200, the intermediate layer 300 and the second connecting layer 400 are all loose structures, and the shell layer 500 is a dense structure. Among them, the overall structural formula of the ternary precursor is Ni x Co y Mn z M a (OH)2, wherein 0.75≤x<1.0, 0≤y<0.18, 0≤z<0.20, 0≤a<0.1, x+y+z+a=1; M is at least one of Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr.
[0080] Based on the first connecting layer, the intermediate layer and the second connecting layer arranged between the core layer and the shell layer, the lithium ion conductivity can be improved, and it is beneficial to buffer and accommodate the stress caused by the volume change during charging and discharging. In combination with the core layer and the shell layer, the material strength and compressive resistance can be improved, thereby reducing resistance and improving battery life, rate performance and cycle stability.
[0081] In some optional embodiments, the porosity of the intermediate layer is less than the porosity of the first connecting layer, and the porosity of the first connecting layer is less than or equal to the porosity of the second connecting layer.
[0082] In order to evaluate the characteristics of porosity, this application uses image analysis software (ImageJ) to directly calculate the pore area and cross-sectional area of each region, and the porosity of different regions is calculated by "porosity = pore area of each region / cross-sectional area of each region × 100%". The porosity in this article is characterized by this method.
[0083] In some optional embodiments, the porosity of the first connecting layer is 6.84%-24.85%, the porosity of the second connecting layer is 7.02%-27.33%, and the porosity of the intermediate layer is 2.27%-10.89%;
[0084] Preferably, the porosity of the first connecting layer is 9.20%-20.07%, the porosity of the second connecting layer is 9.99%-21.78%, and the porosity of the intermediate layer is 3.41%-8.44%.
[0085] For example, the porosity of the first connecting layer can be 6.84%, 8.84%, 10.84%, 12.84%, 14.84%, 16.84%, 18.84%, 20.84%, 22.84%, 24.85% or any value between 6.84% and 24.85%; the porosity of the second connecting layer can be 7.02%, 10.02%, 13.02%, 16.02%, 19.02%, 22.02%, 25.02%, 27.33% or any value between 7.02% and 27.33%; the porosity of the intermediate layer can be 2.27%, 3.27%, 4.27%, 5.27%, 6.27%, 7.27%, 8.27%, 9.27%, 10.89% or any value between 2.27% and 10.89%.
[0086] In some optional embodiments, the average radius of the core layer is 0.90-2.90 μm; the average thickness of the first connecting layer is 0.69-0.92 μm; the average thickness of the middle layer is 1.38-1.85 μm; the average thickness of the second connecting layer is 1.03-1.39 μm; and the average thickness of the shell layer is 2.75-3.69 μm.
[0087] For example, the average radius of the core layer can be 0.90 μm, 1.20 μm, 1.50 μm, 1.80 μm, 2.10 μm, 2.40 μm, 2.70 μm, 2.90 μm or any value between 0.90 and 2.90 μm; the average thickness of the first connecting layer can be 0.69 μm, 0.70 μm, 0.75 μm, 0.80 μm, 0.85 μm, 0.90 μm, 0.92 μm or any value between 0.69 and 0.92 μm; the average thickness of the intermediate layer can be 1.38 μm, 1.40 μm, 1.45 μm, 1.50 μm, 1.55 μm, 1.60 μm, 1.65 μm, 1.70 μm, 1.75 μm, 1.80 μm, 1.90 μm, 2.10 μm, 2.20 μm, 2.30 μm, 2.40 μm, 2.50 μm, 2.60 μm, 2.70 μm, 2.90 μm or any value between 0.90 and 2.90 μm. The average thickness of the second connecting layer can be 1.03μm, 1.05μm, 1.10μm, 1.15μm, 1.20μm, 1.25μm, 1.30μm, 1.35μm, 1.39μm or any value between 1.03-1.39μm; the average thickness of the shell layer can be 2.75μm, 2.80μm, 2.90μm, 3.00μm, 3.10μm, 3.20μm, 3.30μm, 3.40μm, 3.50μm, 3.60μm, 3.69μm or any value between 2.75-3.69μm.
[0088] In some optional embodiments, the center of the core layer is in a loose spherical shape, the outer layer of the core layer except for the center spherical part is in a dense structure, and the primary particles constituting the core layer are in a needle-like shape;
[0089] The primary particles of the middle layer and the shell layer grow radially along the radial direction of the core layer. The primary particles constituting the first connecting layer, the middle layer and the second connecting layer are all needle-shaped, and the primary particles constituting the shell layer are needle-shaped or strip-shaped.
[0090] In this embodiment, due to the limitation of the formation mechanism of the core layer, the center of the core layer presents a loose irregular spherical shape, the outer layer is tightly coated, and the primary particles constituting the core layer are needle-shaped; the middle layer and the shell layer grow radially, that is, the middle layer is a radial structure with a certain porosity, and the shell layer is a dense radial structure; the first connecting layer, the second connecting layer and the middle layer are all composed of needle-shaped filament primary particles; the shell layer is composed of fine needle-shaped or strip-shaped primary particles. Through the orderly connection and growth of the core layer, the first connecting layer, the middle layer, the second connecting layer and the shell layer, the lithium ion conduction inside the particle is smoother, which is conducive to increasing the lithium ion conduction speed, reducing the positive electrode resistance, and improving the rate performance and cycle stability.
[0091] In some optional embodiments, the particle size D50 of the ternary precursor is 13.5-21.5 μm, and the particle size D50 of the ternary precursor is preferably 15.5-19.5 μm; (D90-D10) / D50 is 0.2-0.4, and (D90-D10) / D50 is preferably 0.25-0.35.
[0092] For example, the particle size D50 of the ternary precursor can be 13.5μm, 14.5μm, 15.5μm, 16.5μm, 17.5μm, 18.5μm, 19.5μm, 20.5μm, 21.5μm or any value between 13.5-21.5μm; (D90-D10) / D50 can be 0.2, 0.24, 0.28, 0.32, 0.36, 0.4 or any value between 0.2-0.4.
[0093] In some optional embodiments, the BET specific surface area of the ternary precursor is 12-20 m 2 / g, and the BET specific surface area of the ternary precursor is preferably 13-19m 2 / g.
[0094] For example, the BET surface area of the ternary precursor can be 12 m 2 / g,13m 2 / g,14m 2 / g,15m 2 / g,16m 2 / g,17m 2 / g,18m 2 / g,19m 2 / g,20m 2 / g or 12-20m 2 Any value between / g.
[0095] In some optional embodiments, the tap density TD of the ternary precursor is 1.73-2.13 g / cm 3 ; and the tap density TD of the ternary precursor is preferably 1.83-2.03 g / cm 3 .
[0096] For example, the tap density TD of the ternary precursor can be 1.73 g / cm 3 , 1.75g / cm 3 , 1.80g / cm 3 , 1.85g / cm 3 , 1.90g / cm 3 , 1.95g / cm 3 , 2.00g / cm 3 , 2.05g / cm 3, 2.10g / cm 3 , 2.13g / cm 3 or 1.73-2.13g / cm 3 Any value in between.
[0097] An embodiment of the present invention also provides a method for preparing a ternary precursor, comprising the following steps: adding a ternary mixed solution containing nickel, cobalt, and manganese into a reaction kettle, and adding a pH adjuster and a complexing agent to adjust the reaction solution to a first pH value and a first ammonia concentration, and introducing a protective gas to carry out a first reaction to prepare seed crystals; after the first reaction is completed, changing the feed flow rate of the ternary mixed solution, and adjusting the reaction solution to a second pH value and a second ammonia concentration to carry out a second reaction until the target ternary precursor is obtained.
[0098] By changing the appropriate reaction conditions, the first reaction can form a core layer with a loose center and a dense outer structure, and the second reaction can form a loose first connecting layer, an intermediate layer, a second connecting layer and a dense shell layer. The lithium ion conduction inside the obtained ternary precursor material particles is smoother, and the material's compressive resistance and structural stability can be improved, thereby improving battery performance.
[0099] In some optional embodiments, the feed flow rate of the first reaction is 3.0-6.0% / h; the feed flow rate of the second reaction is 1.0-8.5% / h; the second reaction includes a first stage, a second stage, a third stage and a fourth stage. During the reaction processes of the first stage, the second stage, the third stage and the fourth stage, the feed flow rate of the ternary mixed solution in each stage increases in a step-by-step manner on the basis of the feed flow rate in the previous stage, and the ratio of the step-by-step increase is 2%-100%, that is, the feed flow rate in the latter stage is 2%-100% higher than the feed flow rate in the previous stage; wherein the ratio of the step-by-step increase is preferably 5%-100%.
[0100] Controlling the flow rate of the ternary mixed solution to increase gradually during the first, second, third and fourth stages is beneficial to accelerating the reaction rate of each stage and is beneficial to forming a first connecting layer, an intermediate layer, a second connecting layer and a shell layer with different porosities, thereby forming a ternary precursor material with a multi-layer porous connecting layer and a dense outer shell structure.
[0101] In some optional embodiments, the ternary mixed solution is a ternary solution of Ni, Co, and Mn (molar ratio Ni:Co:Mn=x:y:z, where 0.75≤x<1.0, 0≤y<0.18, 0≤z<0.20, x+y+z=1).
[0102] Preferably, the total concentration of nickel, cobalt and manganese metal ions in the ternary mixed solution is 90-130 g / L. For example, the total concentration of nickel, cobalt and manganese metal ions can be 90 g / L, 95 g / L, 100 g / L, 105 g / L, 110 g / L, 115 g / L, 120 g / L, 125 g / L, 130 g / L or any value between 90 g / L and 130 g / L.
[0103] More preferably, it can be doped, and the doping element M is at least one of Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr. The doping element can be in the form of sulfate or chloride.
[0104] In some optional embodiments, the first pH value is gradually reduced during the first reaction, and the second pH value is gradually increased during the first stage, the second stage, the third stage, and the fourth stage of the second reaction, which is conducive to gradually forming a first connecting layer, an intermediate layer, a second connecting layer, and a dense shell layer of a loose structure. Preferably, the first pH value and the second pH value are both 10.0-12.0. For example, the first pH value and the second pH value can be 10.0, 10.5, 11.0, 11.5, 12.0 or any value between 10.0 and 12.0.
[0105] Preferably, the endpoint pH value of the first pH value is 0.1-0.3 lower than the initial pH value of the first pH value, that is, the initial pH value of the first reaction is 0.1-0.3 lower than the endpoint pH value of the first reaction. For example, the initial pH value of the first reaction can be 0.1, 0.15, 0.2, 0.25, 0.3 or any value between 0.1 and 0.3 lower than the endpoint pH value of the first reaction.
[0106] Preferably, the end point pH value of the second pH value is 0.1-0.4 higher than the initial pH value of the second pH value, that is, the pH value of the fourth stage is 0.1-0.4 higher than the pH value of the first stage. For example, the pH value of the fourth stage can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or any value between 0.1 and 0.4 higher than the pH value of the first stage.
[0107] Preferably, the pH adjuster includes one or more of sodium hydroxide, potassium hydroxide, sodium bicarbonate, and soda ash.
[0108] Preferably, the pH adjuster is a sodium hydroxide aqueous solution with a mass fraction of 25%-60%.
[0109] In some optional embodiments, the first ammonia concentration and the second ammonia concentration are 2.0-7.5 g / L, and the second ammonia concentration is 1.0-3.0 g / L higher than the first ammonia concentration, which is conducive to forming a core layer, a first connecting layer, an intermediate layer, a second connecting layer and a shell layer with a certain porosity.
[0110] Preferably, the complexing agent includes one or more of ammonia water, EDTA, ethylenediamine, sodium citrate, and urea.
[0111] Preferably, the complexing agent is aqueous ammonia with a mass fraction of 15%-45%.
[0112] In some optional embodiments, the reaction temperature during the first reaction and the second reaction is the same;
[0113] In some optional embodiments, the reaction temperature during the first reaction and the second reaction is 45-70° C. For example, the reaction temperature during the first reaction and the second reaction can be 45° C., 50° C., 55° C., 60° C., 65° C., 70° C. or any value between 45° C. and 70° C.
[0114] In some optional embodiments, the first reaction and the second reaction are carried out while stirring, and the stirring speed during the first reaction is maintained unchanged, while the stirring speed during the second reaction is gradually reduced as the reaction proceeds, which is conducive to the rapid formation of a core layer, a first connecting layer, an intermediate layer, a second connecting layer and a shell layer with different porosities.
[0115] In some optional embodiments, the stirring speed of the first reaction is 200-240 r / min, the stirring speed of the second reaction is 30-200 r / min, and the stirring speed at the end of the second reaction is reduced to 30-100 r / min. For example, the stirring speed of the first reaction can be 200r / min, 205r / min, 210r / min, 215r / min, 220r / min, 225r / min, 230r / min, 235r / min, 240r / min or any value between 200r / min and 240r / min; the stirring speed of the second reaction can be 30r / min, 50r / min, 70r / min, 100r / min, 120r / min, 150r / min, 170r / min, 200r / min or any value between 30r / min and 200r / min; the stirring speed at the end of the second reaction can be reduced to 30r / min, 50r / min, 60r / min, 70r / min, 80r / min, 90r / min, 100r / min or any value between 30r / min and 100r / min.
[0116] In the above preparation method, by controlling the stirring speed of the first reaction to maintain a high speed, the stirring speed of the second reaction is gradually reduced, the stirring speed at the end of the second reaction is much lower than the starting stirring speed, the pH of the second reaction is gradually increased, the pH at the end of the second reaction is 0.1-0.4 higher than the initial pH, the ammonia concentration of the second reaction is 1.0-3.0 g / L higher than the ammonia concentration of the first reaction, and other reaction conditions, a ternary precursor material with a multi-layer porous connecting layer and a dense shell structure can be obtained, and the second reaction adjusts the reaction flow ratio at a certain reaction time node, which is conducive to the formation of connecting layers with different pores. The second reaction gradually reduces the stirring intensity and increases the pH, reduces the supersaturation of the solution, is conducive to the rapid growth of crystals on the interface, and is conducive to the stability of the crystal particle strength.
[0117] In some optional embodiments, the seed particle size D50 obtained after the first reaction is completed is 1.8-5.8 μm, and the seed particle size D50 obtained after the first reaction is completed is preferably 2.8-4.8 μm. For example, the seed particle size D50 after the first reaction is completed can be 1.8 μm, 2.8 μm, 3.8 μm, 4.8 μm, 5.8 μm or any value between 1.8 μm and 5.8 μm.
[0118] In some optional embodiments, the particle size D50 of the ternary precursor obtained after the second reaction is completed is 13.5-21.5 μm, and the particle size D50 of the ternary precursor obtained after the second reaction is completed is preferably 15.5-19.5 μm. For example, the particle size D50 of the ternary precursor after the second reaction is completed can be 13.5 μm, 14 μm, 15 μm, 16 μm, 16.5 μm, 17 μm, 17.5 μm, 18 μm, 18.5 μm, 19 μm, 20.5 μm, 21.5 μm or any value between 13.5 μm and 21.5 μm.
[0119] In some optional embodiments, the method for preparing the ternary precursor of the embodiment of the present invention specifically includes the following steps:
[0120] 1. First reaction: A ternary mixed solution of nickel, cobalt and manganese metal raw materials is prepared with a certain proportion and concentration, and liquid alkali (pH regulator) and ammonia complexing agent are added, and the mixture is reacted for a certain period of time under nitrogen protection to obtain a core layer.
[0121] 2. Second reaction: Continue the reaction on the seed dry material obtained in the first reaction, adjust the process conditions including reaction flow, pH, ammonia concentration, and carry out the reaction in stages. After a certain period of reaction in each stage, the particles reach the required particle size, and then proceed to the next stage of reaction until a positive electrode material precursor material with a multi-layer porous connected layer structure that meets the particle size requirements is finally obtained.
[0122] The slurry obtained by the reaction is then subjected to solid-liquid separation, aging, dehydration, drying, screening and other operations to obtain the target product.
[0123] The present invention also provides a ternary positive electrode material, which is prepared using any of the ternary precursors described above. For example, the ternary positive electrode material can be prepared by mixing and sintering the ternary precursor described above with a lithium salt.
[0124] The present invention also provides a battery positive electrode, comprising the above-mentioned ternary positive electrode material.
[0125] The present invention also provides a lithium ion battery, comprising the above-mentioned battery positive electrode.
[0126] The present invention also provides an electrical device, comprising the above-mentioned lithium-ion battery. The electrical device can be powered by the lithium-ion battery of the present invention or can charge the lithium-ion battery of the present invention.
[0127] In order to make the purpose, technical solutions and beneficial effects of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. However, the described specific embodiments are only used to explain the present invention and are not used to limit the present invention.
[0128] Example 1
[0129] Preparation of a cathode material precursor material with a multi-layer porous connecting layer and a dense shell structure, synthesizing the chemical formula Ni 0.80 Co 0.10 Mn 0.10 (OH)2.
[0130] 1. Material selection: Nickel sulfate, cobalt sulfate and manganese sulfate are used. The metal raw materials are prepared into a mixed metal salt solution with a concentration of 110 g / L according to the molar ratio of nickel, cobalt and manganese of 0.80:0.10:0.10.
[0131] 2. The first step: add a certain amount of pure water, ammonia water and liquid alkali to the 1# reactor to adjust the ammonia concentration and pH, adjust the system ammonia concentration to 3.5g / L, and the pH to 11.4; the reaction temperature is raised to 55°C, the stirring speed is controlled at 220r / min, and under the protection of inert gas nitrogen, the nickel-cobalt-manganese ternary metal mixed solution, liquid alkali and ammonia water are introduced simultaneously for co-precipitation reaction. The ternary metal flow rate is 5.0% / h of the effective volume of the reactor, and the pH is controlled to be lowered during the reaction process to form a loose central layer of a certain size, and the end point pH is adjusted to 11.2. When the particle size D50 reaches 3.8μm, stop feeding. A ternary precursor material (core layer) with a loose center and a compact structure coated on top is obtained.
[0132] 3. The second step: transfer the dehydrated dry base material of the slurry in the first step into the 2# reactor, add pure water, ammonia water and liquid alkali, adjust the ammonia concentration and pH value, the system ammonia concentration is 5.0g / L, the pH is 10.50, the temperature is raised to 55°C, the stirring speed is controlled at 190r / min, and the ternary metal mixed solution, ammonia solution and sodium hydroxide solution are introduced at the same time under the protection of inert gas nitrogen for co-precipitation reaction. Among them, the flow rate of the ternary metal and the pH value at different stages of the reaction process are adjusted to continue the reaction.
[0133] In the first stage, the ternary metal flow rate is 1.5% / h of the effective volume of the reactor, forming a first connection layer with a certain porosity; in the second stage, the ternary metal flow rate is 2.0% / h of the effective volume of the reactor, forming an intermediate layer with a certain porosity; in the third stage, the ternary metal flow rate is 3.0% / h of the effective volume of the reactor, forming a second connection layer with a certain porosity; in the fourth stage, the ternary metal flow rate is 3.5% / h of the effective volume of the reactor until the reaction particle size reaches the requirement, and the pH of the reaction system gradually increases, and the end point pH rises to 10.7. During the reaction, the stirring speed gradually decreases, and the end point speed is 40r / min. The reaction is continued to obtain a dense and radiated shell layer; when the slurry particle size D50 reaches the requirement of 17-18μm, the feeding is stopped. A positive electrode material precursor material with a multi-layer porous connection layer and a dense shell structure is obtained.
[0134] Post-treatment: After stopping the reaction, wash the material with an appropriate amount of dilute alkali and pure water, dry, sieve through a 400-mesh sieve, and package and seal. Thus, a ternary precursor material with multiple porous connecting layers and a dense shell structure is obtained. Figure 2 This is a cross-sectional view of the ternary precursor obtained in Example 1.
[0135] Example 2
[0136] Prepare a cathode material precursor with multi-layer porous connecting layer and dense shell structure, synthesize chemical formula Ni 0.846 Co 0.10 Mn 0.05 Zr 0.004 (OH)2.
[0137] 1. Select materials: Use nickel sulfate, cobalt sulfate, manganese sulfate, and zirconium sulfate. The metal raw materials are prepared into a 110g / L mixed ternary metal salt solution according to the molar ratio of nickel, cobalt, and manganese of 0.846:0.10:0.05. Zirconium sulfate, sodium citrate, and sulfuric acid are prepared into a 1.37g / L zirconium solution.
[0138] 2. The first step: add a certain amount of pure water, ammonia water and liquid alkali to the 1# reactor to adjust the ammonia concentration and pH, adjust the system ammonia concentration to 3.5g / L, and the pH to 11.3; the reaction temperature rises to 55°C, the stirring speed is controlled at 220r / min, and under the protection of inert gas nitrogen, the nickel-cobalt-manganese ternary metal mixed solution, zirconium solution, liquid alkali, and ammonia water are introduced simultaneously for coprecipitation reaction. The ternary metal flow rate is 5.0% / h of the effective volume of the reactor, and the zirconium solution flow rate is 2.5% / h. The pH is controlled to be lowered during the reaction process to form a loose center layer of a certain size, and the end point pH is adjusted to 11.2. When the particle size D50 reaches 4.24μm, stop feeding to obtain a ternary precursor material (core layer) with a loose center and a compact structure coated on top.
[0139] 3. The second step: transfer the dehydrated dry base material of the slurry in the first step into the 2# reactor, add a certain amount of pure water, ammonia water and liquid alkali, adjust the ammonia concentration and pH value, the system ammonia concentration is 5.0g / L, the pH is 10.60, the temperature is raised to 55°C, the stirring speed is controlled at 190r / min, and the ternary metal mixed solution, zirconium solution, ammonia solution and sodium hydroxide solution are introduced at the same time under the protection of inert gas nitrogen for co-precipitation reaction. Among them, the flow rate of the ternary metal and the pH value at different stages of the reaction process are adjusted to continue the reaction.
[0140] In the first stage, the ternary metal flow rate is 2.0% / h of the effective volume of the reactor, and the zirconium solution flow rate is 1.0% / h, forming a first connection layer with a certain porosity; in the second stage, the ternary metal flow rate is 2.5% / h of the effective volume of the reactor, and the zirconium solution flow rate is 1.25% / h, forming an intermediate layer with a certain porosity; in the third stage, the ternary metal flow rate is 3.5% / h of the effective volume of the reactor, and the zirconium solution flow rate is 1.75% / h, forming a second connection layer with a certain porosity; in the fourth stage, the ternary metal flow rate is 4.0% / h of the effective volume of the reactor, and the zirconium solution flow rate is 2.0% / h until the reaction particle size reaches the requirement, and the pH of the reaction system gradually increases, and the end point pH rises to 10.8, the stirring speed gradually decreases during the reaction, and the end point speed is 40r / min, and the reaction is continued to obtain a dense and radiated shell layer; when the slurry particle size D50 reaches the requirement of 18-19μm, the feeding is stopped. A positive electrode material precursor material with a multi-layer porous connection layer and a dense shell structure is obtained.
[0141] Post-treatment: After stopping the reaction, wash the material with an appropriate amount of dilute alkali and pure water, dry, sieve through a 400-mesh sieve, and package and seal. Thus, a ternary precursor material with multiple porous connecting layers and a dense shell structure is obtained. Figure 3 This is a cross-sectional view of the ternary precursor obtained in Example 2.
[0142] Example 3
[0143] Prepare a cathode material precursor with multi-layer porous connecting layer and dense shell structure, synthesize chemical formula Ni 0.90 Co 0.05 Mn 0.05 (OH)2.
[0144] 1. Select nickel sulfate, cobalt sulfate and manganese sulfate as materials. The metal raw materials are prepared into a ternary mixed metal salt solution with a concentration of 110 g / L according to the molar ratio of nickel, cobalt and manganese of 0.90:0.05:0.05.
[0145] 2. The first step: add pure water, ammonia water and liquid alkali to the 1# reactor to adjust the ammonia concentration and pH, adjust the system ammonia concentration to 3.5g / L, and the pH to 11.4; the reaction temperature is raised to 55°C, the stirring speed is controlled at 220r / min, and under the protection of inert gas nitrogen, the nickel-cobalt-manganese ternary metal mixed solution, liquid alkali, and ammonia water are introduced simultaneously for co-precipitation reaction. The ternary metal flow rate is 4.0% / h of the effective volume of the reactor, and the pH is controlled to be lowered during the reaction process to form a loose center layer of a certain size, and the end point pH is adjusted to 11.3. When the equal particle size D50 reaches 3.06μm, stop feeding to obtain a ternary precursor material (core layer) with a loose center and a compact structure coated on top.
[0146] 3. The second step: transfer the slurry dehydrated dry base material from the first step into the 2# reactor, add pure water, ammonia water and liquid alkali, adjust the ammonia concentration and pH value, the system ammonia concentration is 5.0g / L, the pH is 10.70, the temperature is raised to 55°C, the stirring speed is controlled at 190r / min, and the ternary metal mixed solution, ammonia solution and sodium hydroxide solution are introduced at the same time under the protection of inert gas nitrogen for co-precipitation reaction. Among them, the ternary metal flow rate and pH value at different stages of the reaction process are adjusted to continue the reaction.
[0147] In the first stage, the ternary metal flow rate is 3.0% / h of the effective dissolution of the reactor, forming a first connection layer with a certain porosity; in the second stage, the ternary metal flow rate is 4.0% / h of the effective dissolution of the reactor, forming an intermediate layer with a certain porosity; in the third stage, the ternary metal flow rate is 5.5% / h of the effective dissolution of the reactor, forming a second connection layer with a certain porosity; in the fourth stage, the ternary metal flow rate is 6.5% / h of the effective dissolution of the reactor until the particle size reaches the requirement, and the pH of the reaction system gradually increases, and the end point pH rises to 10.8. During the reaction, the stirring speed gradually decreases, and the end point speed is 40r / min. The reaction is continued to obtain a dense and radiated shell layer; when the slurry particle size D50 reaches the requirement of 16-17μm, the feeding is stopped. A positive electrode material precursor material with a multi-layer porous connection layer and a dense shell structure is obtained.
[0148] Post-treatment: After stopping the reaction, wash the material with an appropriate amount of dilute alkali and pure water, dry, sieve through a 400-mesh sieve, and package and seal. Thus, a ternary precursor material with multiple porous connecting layers and a dense shell structure is obtained. Figure 4 This is a cross-sectional view of the ternary precursor obtained in Example 3.
[0149] Example 4
[0150] Prepare a cathode material precursor with multi-layer porous connecting layer and dense shell structure, synthesize chemical formula Ni 0.95 Co 0.03 Mn 0.02 (OH)2.
[0151] 1. Material selection: nickel sulfate, cobalt sulfate and manganese sulfate are used. The metal raw materials are prepared into a ternary mixed metal salt solution with a concentration of 110g / L according to the molar ratio of nickel, cobalt and manganese of 0.95:0.03:0.02.
[0152] 2. The first step: add pure water, ammonia water and liquid alkali to the 1# reactor to adjust the ammonia concentration and pH, adjust the system ammonia concentration to 3.5g / L, and the pH to 11.4; the reaction temperature is raised to 55°C, the stirring speed is controlled at 220r / min, and under the protection of inert gas argon, a nickel-cobalt-manganese ternary metal mixed solution, liquid alkali, and ammonia water are introduced simultaneously for coprecipitation reaction. The ternary metal flow rate is 5.0% / h of the effective volume of the reactor, and the pH is controlled to be lowered during the reaction process to form a loose center layer of a certain size, and the end point pH is adjusted to 11.2. When the particle size D50 reaches 2.40μm, stop feeding to obtain a ternary precursor material (core layer) with a loose center and a compact structure coated on top.
[0153] 3. The second step: transfer the dehydrated dry base material of the slurry in the first step into the 2# reactor and add pure water to 5.0m 3 , add ammonia water and liquid alkali, adjust the ammonia concentration and pH value, the system ammonia concentration is 5.0g / L, the pH is 10.7, the temperature rises to 55°C, the stirring speed is controlled at 190r / min, and the ternary metal mixed solution, ammonia solution, and sodium hydroxide solution are introduced simultaneously under the protection of inert gas nitrogen for co-precipitation reaction. Among them, the ternary metal flow rate and pH value at different stages of the reaction process are adjusted to continue the reaction.
[0154] In the first stage, the ternary metal flow rate is 4.0% / h of the effective dissolution of the reactor, forming a first connection layer with a certain porosity; in the second stage, the ternary metal flow rate is 5.0% / h of the effective dissolution of the reactor, forming an intermediate layer with a certain porosity; in the third stage, the ternary metal flow rate is 7.0% / h of the effective dissolution of the reactor, forming a second connection layer with a certain porosity; in the fourth stage, the ternary metal flow rate is 8.0% / h of the effective dissolution of the reactor until the reaction particle size reaches the requirement, and the pH of the reaction system gradually increases, raising the end point pH to 10.9, the stirring speed gradually decreases during the reaction, the end point speed is 40r / min, and the reaction is continued to obtain a dense and radiated shell layer; when the slurry particle size D50 reaches the requirement of 17-18μm, the feeding is stopped. A positive electrode material precursor material with a multi-layer porous connection layer and a dense shell structure is obtained.
[0155] Post-treatment: After stopping the reaction, wash the material with an appropriate amount of dilute alkali and pure water, dry, sieve through a 400-mesh sieve, and package and seal. Thus, a ternary precursor material with multiple porous connecting layers and a dense shell structure is obtained. Figure 5 This is a cross-sectional view of the ternary precursor obtained in Example 4.
[0156] Comparative Example 1
[0157] Prepare a three-layer positive electrode material precursor with a porous connecting layer and a dense outer shell structure, and synthesize the chemical formula Ni 0.80 Co 0.10 Mn 0.10 (OH)2.
[0158] 1. Material selection: nickel sulfate, cobalt sulfate and manganese sulfate are used. The metal raw materials are prepared into a ternary mixed metal salt solution with a concentration of 110g / L according to the molar ratio of nickel, cobalt and manganese of 0.80:0.10:0.10.
[0159] 2. Step 1: Add pure water, ammonia water and liquid alkali to the 1# reactor to adjust the ammonia concentration and pH, adjust the system ammonia concentration to 4.5g / L and the pH to 11.7; the reaction temperature rises to 60°C, and the stirring speed is controlled at 220r / min; simultaneously, introduce a nickel-cobalt-manganese ternary metal mixed solution, liquid alkali and ammonia water for coprecipitation reaction. The ternary metal flow rate is 4.0% / h of the effective dissolution of the reactor, and the pH is controlled to be lowered during the reaction process. The end point pH is adjusted to 11.0, and the feeding is stopped when the particle size D50 reaches 4.5μm. A ternary precursor (core layer) with a compact structure coated on a central loose layer is obtained.
[0160] 3. The second step: transfer the dehydrated dry base material of the slurry in the first step into the 2# reactor, add pure water, ammonia water and liquid alkali, adjust the ammonia concentration and pH value, the system ammonia concentration is 4.5g / L, the pH is 10.7 in the initial stage, the temperature is raised to 60°C, the stirring speed is controlled at 220r / min, and the ternary metal mixed solution, ammonia solution and sodium hydroxide solution are introduced at the same time for co-precipitation reaction; the initial ternary metal flow rate is 2.0% / h of the effective volume of the reactor, and the terminal ternary metal flow rate is 6.0% / h of the effective volume of the reactor. During the reaction, the stirring speed gradually decreases, and the terminal speed is 100r / min; the system pH decreases during the reaction process, the terminal pH is 10.6, and the ammonia concentration remains unchanged; when the slurry particle size D50 reaches 17-18μm, stop feeding.
[0161] Post-treatment: After the reaction is stopped, the material is washed with an appropriate amount of dilute alkali and pure water, dried, sieved through a 400-mesh sieve, and packaged and sealed. Thus, a positive electrode material precursor with three layers, one porous connecting layer and a dense outer shell structure is obtained. Figure 6 This is a cross-sectional view of the ternary precursor obtained in Comparative Example 1.
[0162] Comparative Example 2
[0163] Prepare a positive electrode material precursor with no internal connection layer and porous structure, synthesize the chemical formula Ni 0.846 Co 0.10 Mn 0.05 Zr 0.004 (OH)2.
[0164] 1. Material selection: Nickel sulfate, cobalt sulfate and manganese sulfate are used. The metal raw materials are prepared into a ternary mixed metal salt solution with a concentration of 110g / L according to the molar ratio of nickel, cobalt and manganese of 0.846:0.10:0.05; zirconium sulfate, sodium citrate and sulfuric acid are prepared into a zirconium solution with a concentration of 1.37g / L.
[0165] 2. The first step: pure water, ammonia water and liquid alkali are added to the 1# reactor to adjust the ammonia concentration and pH, and the system ammonia concentration is adjusted to 4.5g / L and the pH is 11.7; the reaction temperature is raised to 60°C, and the stirring speed is controlled at 220r / min. After the conditions are met, a nickel-cobalt-manganese ternary metal mixed solution, a zirconium solution, liquid alkali and ammonia water are introduced simultaneously for co-precipitation reaction. The flow rate of the ternary metal is 4.0% / h of the effective volume of the reactor, and the flow rate of the zirconium solution is 2.0% / h. The pH is controlled to be lowered during the reaction process, and the end point pH is adjusted to 11.0. When the particle size D50 reaches 4.7μm, the feeding is stopped. A ternary precursor (core layer) with a compact structure coated on a central loose layer is obtained.
[0166] 3. The second step: transfer the dehydrated dry base material of the slurry in the first step into the 2# reactor, add pure water, ammonia water and liquid alkali, adjust the ammonia concentration and pH value, the system ammonia concentration is 4.5g / L, the pH is 10.6 in the initial stage, the temperature is raised to 60°C, the stirring speed is controlled at 220r / min, and the ternary metal mixed solution, ammonia solution and sodium hydroxide solution are introduced at the same time for co-precipitation reaction; the initial ternary metal flow rate is 3.0% / h of the effective volume of the reactor and the initial zirconium solution flow rate is 1.5% / h, the terminal ternary metal flow rate is 6.0% / h of the effective volume of the reactor and the terminal zirconium solution flow rate is 3.0% / h, the stirring speed gradually decreases during the reaction, and the terminal speed is 100r / min; the system pH rises during the reaction process, the terminal pH is 10.7, and the ammonia concentration remains unchanged; when the slurry particle size D50 reaches 17-18μm, stop feeding.
[0167] Post-treatment: After the reaction is stopped, the material is washed with an appropriate amount of dilute alkali and pure water, dried, sieved through a 400-mesh sieve, and packaged and sealed. Thus, a positive electrode material precursor with a porous structure without an internal connection layer is obtained. Figure 7 This is a cross-sectional view of the ternary precursor obtained in Comparative Example 2.
[0168] Comparative Example 3
[0169] Prepare a positive electrode material precursor with no internal connection layer and compact structure, synthesize the chemical formula Ni 0.80 Co 0.10 Mn 0.10 (OH)2.
[0170] 1. Material selection: nickel sulfate, cobalt sulfate and manganese sulfate are used. The metal raw materials are prepared into a ternary mixed metal salt solution with a concentration of 110g / L according to the molar ratio of nickel, cobalt and manganese of 0.80:0.10:0.10.
[0171] 2. Step 1: Add pure water, ammonia water and liquid alkali to the 1# reactor to adjust the ammonia concentration and pH, adjust the system ammonia concentration to 5.0g / L and pH to 11.1; the reaction temperature is raised to 55°C, the stirring speed is controlled at 220r / min, and the nickel-cobalt-manganese ternary metal mixed solution, liquid alkali and ammonia water are introduced at the same time for coprecipitation reaction. The reaction maintains the ternary metal flow rate at 4.0% / h of the effective volume of the reactor, and maintains the particle size D50 within the range of 3.0-4.0μm to obtain a ternary precursor with a compact interior.
[0172] 3. Second step: quantitatively transfer 5.0m3 of the first step storage tank from the 2# reactor 3Slurry, add ammonia water and liquid alkali to adjust the ammonia concentration and pH, adjust the system ammonia concentration to 5.0g / L, pH to 10.8; the reaction temperature is raised to 55°C, the stirring speed is controlled at 200r / min, and under the protection of inert gas nitrogen, nickel, cobalt and manganese ternary metal mixed solution, liquid alkali and ammonia water are introduced simultaneously for co-precipitation reaction. During the reaction process, the ternary metal flow rate is 5.0% / h of the effective volume of the reactor, the ternary flow rate remains unchanged, the stirring speed remains unchanged, and the pH and ammonia concentration remain unchanged. When the slurry particle size D50 reaches 17-18μm, stop feeding. A positive electrode material precursor with no radial connection layer and a compact internal structure is obtained. Figure 8 This is a cross-sectional view of the ternary precursor obtained in Comparative Example 3.
[0173] Table 1 shows the structural characteristics of each layer of the ternary precursor in the above examples and comparative examples.
[0174]
[0175] Table 2 shows the average thickness of each layer structure of the ternary precursor in the above examples and comparative examples.
[0176]
[0177] Table 3 shows the physicochemical properties of the ternary precursors in the above examples and comparative examples.
[0178]
[0179] according to Figure 1-8 As shown in Tables 1-3, compared with the comparative example, the specific surface areas of Examples 1, 2, 3, and 4 are between 15 and 18 m 2 / g, high BET is beneficial to increase the contact area between particles and electrolyte, thereby improving battery performance.
[0180] The ternary precursor particles in Examples 1, 2, 3, and 4 are all five-layer structures, with two porous connecting layers and a dense structure shell, the particles grow radially from the inside to the outside, and the porosity of the middle layer is less than that of the first connecting layer, and the porosity of the first connecting layer is less than or equal to the second connecting layer. The particles in the middle layer grow radially and are connected to the core layer and the shell layer through the first connecting layer and the second connecting layer, respectively, which can provide a lithium ion conduction channel inside the particle, and the high BET and the first connecting layer and the second connecting layer with two different pores are conducive to increasing the reaction area with the electrolyte and improving the lithium ion conduction efficiency, thereby significantly reducing the positive electrode resistance, improving the rate performance and the cycle stability. In addition, the two porous connecting layers can buffer and accommodate the stress caused by the volume change caused during charging and discharging, and at the same time, the compact core layer and the dense radial shell structure can withstand the stress generated by cyclic charging and discharging, improve the compressive strength and structural stability, and improve the life and safety performance of the battery.
[0181] Performance Testing
[0182] 2000 g of the precursor prepared in the embodiment and the comparative example and LiOH·H2O were mixed uniformly in a high-speed mixer at a molar ratio of 1:1.03, and sintered in a box furnace under air atmosphere at a sintering temperature of 780°C for 12 h. After cooling to room temperature, the mixture was crushed and sieved to obtain a nickel-cobalt-manganese ternary positive electrode material.
[0183] The electrochemical performance test was conducted using a button-type semi-battery: the above-mentioned positive electrode material, conductive carbon black, and binder PVDF (polyvinylidene fluoride) were mixed into a slurry at a ratio of 8:1:1, and coated on aluminum foil to make a positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1). The battery shell, positive and negative electrode sheets, diaphragms, springs, and gaskets were assembled into a button-type battery in a vacuum glove box. The electrochemical performance test was conducted using a blue electric test system.
[0184] At room temperature, the 1C cycle test was carried out for 50 weeks at 3.0-4.3V. The electrochemical performance is shown in Table 2:
[0185] Table 4 shows the electrochemical performance of the ternary precursors in the above examples and comparative examples.
[0186]
[0187] It can be seen from the electrochemical properties in Table 4 that compared with Comparative Examples 1, 2, and 3, the resistance of the positive electrode material in Examples 1-4 is reduced by 2-8 (Ω), and the resistance amplitude is reduced, which is beneficial to improving the battery life. In addition, the 50-week cycle retention rate of the electrochemical performance of Examples 1-4 is improved by 2.7%-5.3%, and the rate performance is improved by 2.72%-5.3%; the first discharge capacity is improved to a certain extent, by 5.4mAh / g-15.3mAh / g, and the first charge and discharge efficiency is improved by 2.3%-7.3%. The improvement in the first efficiency is beneficial to improving the battery energy density. It can be seen that the various electrochemical properties of the ternary precursor material with a dense shell structure of a multi-layer porous connecting layer of Examples 1-4 are significantly improved compared with the electrochemical properties of the comparative example, and the ternary positive electrode material of the present invention has better excellent performance.
[0188] The various technical features described above can be combined arbitrarily. Although all possible combinations of these technical features are not described, any combination of these technical features should be considered to be covered by this specification as long as there is no contradiction in such combination.
[0189] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A ternary precursor, characterized in that: The ternary precursor is nickel-cobalt-manganese hydroxide; The ternary precursor includes a core layer, a shell layer, and a multi-layer connecting layer between the core layer and the shell layer, wherein the core layer and the shell layer are dense structures, and the multi-layer connecting layers are loose structures; the multi-layer connecting layers include a first connecting layer, an intermediate layer, and a second connecting layer from the inside to the outside; The porosity of the middle layer is less than that of the first connecting layer, and the porosity of the first connecting layer is less than or equal to that of the second connecting layer; the porosity of the first connecting layer is 6.84%-24.85%, the porosity of the second connecting layer is 7.02%-27.33%, and the porosity of the middle layer is 2.27%-10.89%.
2. The ternary precursor according to claim 1, characterized in that: The chemical formula of the ternary precursor is Ni x Co y Mn z M a (OH)2, wherein 0.75≤x<1.0, 0≤y<0.18, 0≤z<0.20, 0≤a<0.1, x+y+z+a=1; and M is at least one of Al, Ti, Zr, Mo, Cr, W, B, Mg, Ba, Nb and Sr.
3. The ternary precursor according to claim 1 or 2, characterized in that: The porosity of the first connecting layer is 9.20%-20.07%, the porosity of the second connecting layer is 9.99%-21.78%, and the porosity of the intermediate layer is 3.41%-8.44%.
4. The ternary precursor according to claim 1 or 2, characterized in that: The average radius of the core layer is 0.90-2.90 μm; The average thickness of the first connecting layer is 0.69-0.92 μm; The average thickness of the intermediate layer is 1.38-1.85 μm; The average thickness of the second connecting layer is 1.03-1.39 μm; The average thickness of the shell layer is 2.75-3.69 μm.
5. The ternary precursor according to claim 1 or 2, characterized in that: The primary particles constituting the core layer, the first connecting layer, the intermediate layer and the second connecting layer are all in the shape of needle strips, and the primary particles constituting the shell layer are in the shape of needle strips or strips; The primary particles constituting the intermediate layer and the shell layer grow radially.
6. The ternary precursor according to claim 1 or 2, characterized in that: The particle size D50 of the ternary precursor is 13.5-21.5 μm.
7. The ternary precursor according to claim 6, characterized in that: The particle size D50 of the ternary precursor is 15.5-19.5 μm.
8. The ternary precursor according to claim 1 or 2, characterized in that: The specific surface area of the ternary precursor is 12-20m 2 / g.
9. The ternary precursor according to claim 8, characterized in that: The specific surface area of the ternary precursor is 13-19 m 2 / g.
10. The ternary precursor according to claim 1 or 2, characterized in that: The tap density of the ternary precursor is 1.73-2.13 g / cm 3 .
11. The ternary precursor according to claim 10, characterized in that The tap density of the ternary precursor is 1.83-2.03 g / cm 3 .
12. The ternary precursor according to claim 1 or 2, characterized in that: The particle size distribution of the ternary precursor (D90-D10) / D50 is 0.2-0.
4.
13. A method for preparing a ternary precursor as claimed in any one of claims 1 to 12, characterized in that: The method comprises the following steps: adding a ternary mixed solution containing nickel, cobalt and manganese into a reaction kettle, adding a pH regulator and a complexing agent to adjust the reaction solution to a first pH value and a first ammonia concentration, and introducing a protective gas to carry out a first reaction to prepare a seed crystal; After the first reaction is completed, the feed flow rate of the ternary mixed solution is changed, and the reaction solution is adjusted to a second pH value and a second ammonia concentration to perform a second reaction until the ternary precursor is obtained; The feed flow rate of the first reaction is 3.0-6.0% / h; The feed flow rate of the second reaction is 1.0-8.5% / h; The second reaction includes a first stage, a second stage, a third stage and a fourth stage. During the reaction processes of the first stage, the second stage, the third stage and the fourth stage, the feed flow rate of the ternary mixed solution in each stage increases stepwise on the basis of the feed flow rate in the previous stage, and the stepwise increase ratio is 2%-100%; During the first reaction, the first pH value is adjusted to gradually decrease, and during the first stage, the second stage, the third stage and the fourth stage of the second reaction, the second pH value is adjusted to gradually increase; The first pH value and the second pH value are both 10.0-12.0; The ammonia concentration during the first reaction and the second reaction is 2.0-7.5 g / L 。 14. The method for preparing a ternary precursor according to claim 13, characterized in that: The total concentration of nickel, cobalt and manganese metal ions in the ternary mixed solution is 90-130 g / L.
15. The method for preparing a ternary precursor according to claim 13 or 14, characterized in that: The ratio of the step-wise increase in the second reaction is 5%-100%.
16. The method for preparing a ternary precursor according to claim 13 or 14, characterized in that: The first reaction and the second reaction are carried out while stirring, and the stirring speed in the first reaction remains unchanged, while the stirring speed in the second reaction gradually decreases as the reaction proceeds.
17. The method for preparing a ternary precursor according to claim 16, characterized in that: The stirring speed of the first reaction is 200-240 r / min, the stirring speed of the second reaction is 30-200 r / min, and the stirring speed at the end of the second reaction is reduced to 30-100 r / min.
18. The method for preparing a ternary precursor according to claim 13 or 14, characterized in that: The seed crystal particle size D50 after the first reaction is completed is 1.8-5.8 μm.
19. The method for preparing a ternary precursor according to claim 13 or 14, characterized in that: After the second reaction is completed, the particle size D50 of the ternary precursor material is 13.5-21.5 μm.
20. The method for preparing a ternary precursor according to claim 13 or 14, characterized in that: The endpoint pH value of the first pH value is 0.1-0.3 lower than the initial pH value of the first pH value.
21. The method for preparing a ternary precursor according to claim 13 or 14, characterized in that: The endpoint pH value of the second pH value is 0.1-0.4 higher than the initial pH value of the second pH value.
22. The method for preparing a ternary precursor according to claim 13 or 14, characterized in that: The second reaction ammonia concentration is 1.0-3.0 g / L higher than the first reaction ammonia concentration.
23. A positive electrode material for a battery, characterized in that: The ternary precursor according to any one of claims 1 to 12 is prepared by mixed sintering with a lithium salt.
Citation Information
Patent Citations
Tantalum-doped nickel-cobalt-aluminum ternary precursor and preparation method thereof, lithium ion battery positive electrode material and lithium ion battery
CN112701263A
Nickel-cobalt-manganese ternary material, precursor thereof, preparation method of precursor, and application of material
CN112928250A
Cited By
Preparation method of solid-state battery positive electrode material precursor with multi-layer segmented structure
CN121317908A